Ferritin Light Chain: A Candidate Autoantigen in Immuno-Related Pancytopenia - Zhang, Yang; Hao, Shanfeng; Xiao, Na; Zhang, Yu; Wang, Huaquan; Li, Lijuan; Fu, Rong; Shao, Zonghong (Frontiers in Immunology, 2022)
The characteristic feature of immune-related pancytopenia (IRP) is autoantibody-mediated bone marrow damage and peripheral blood cytopenia. We found the potential antigen of IRP was FTL by SEREX (serological analysis of recombinant cDNA expression libraries) in the previous study. In this study, we tried to explore the antigenic epitopes of FTL and verify its antigenicity in IRP. We found the possible FTL epitope: VNLYLQASYTYLSLG by phage random peptide library. Through ELISPOT, it was found that peptide VNLYLQASYTYLSLG can significantly stimulate the production of IL-4 and cannot stimulate the production of IFN-γ, which suggested that the peptide can obviously activate Th2 cells. Peptide-MHC-tetramer elicited antigen-specific T cell responses. The expression levels of FTL were significantly increased in the untreated IRP patients(P<0.05). In conclusion, we found that FTL is the target antigen for some IRP patients. The peptide of VNLYLQASYTYLSLG is an epitope of the target antigen. The target antigen is abnormally overexpressed on the membrane of bone marrow (BM) cells, especially on the surface of CD34+ BM cells of IRP patients. And it is related to the severity of disease. These results provide a possible new target for the treatment of IRP in the future.